Chesapeake Bay fish–osprey (Pandion haliaetus) food chain: Evaluation of contaminant exposure and genetic damage. (1st April 2016) - Lazarus, Rebecca S.; Rattner, Barnett A.; McGowan, Peter C.; Hale, Robert C.; Karouna‐Renier, Natalie K.; Erickson, Richard A.; Ottinger, Mary Ann
Abstract: From 2011 to 2013, a large‐scale ecotoxicological study was conducted in several Chesapeake Bay (USA) tributaries (Susquehanna River and flats, the Back, Baltimore Harbor/Patapsco Rivers, Anacostia/ middle Potomac, Elizabeth and James Rivers) and Poplar Island as a mid‐Bay reference site. Osprey ( Pandion haliaetus ) diet and the transfer of contaminants from fish to osprey eggs were evaluated. The most bioaccumulative compounds (biomagnification factor > 5) included p, p′ ‐dichlorodiphenyldichloroethylene (DDE), total polychlorinated biphenyls (PCBs), total polybrominated diphenyl ethers (PBDEs), and bromodiphenyl ether (BDE) congeners 47, 99, 100, and 154. This analysis suggested that alternative brominated flame retardants and other compounds (methoxytriclosan) are not appreciably biomagnifying. A multivariate analysis of similarity indicated that major differences in patterns among study sites were driven by PCB congeners 105, 128, 156, 170/190, and 189, and PBDE congeners 99 and 209. An integrative redundancy analysis showed that osprey eggs from Baltimore Harbor/Patapsco River and the Elizabeth River had high residues of PCBs and p, p ′‐DDE, with PBDEs making a substantial contribution to overall halogenated contamination on the Susquehanna and Anacostia/middle Potomac Rivers. The redundancy analysis also suggested a potential relation between PBDE residues in osprey eggs and oxidative DNA damage in nestling blood samples. The results also indicate that there is no longer a discernible relation between halogenated contaminants in osprey eggs and their reproductive success in Chesapeake Bay. Osprey populations are thriving in much of the Chesapeake, with productivity rates exceeding those required to sustain a stable population. Environ Toxicol Chem 2016;35:1560–1575. Published 2016 Wiley Periodicals Inc. on behalf of SETAC. This article is a US Government work and, as such, is in the public domain in the United States of America.